Strategi Pengembangan Potensi Wisata Desa Bone-Bone Kabupaten Enrekang Provinsi Sulawesi Selatan - Aprilya Fitriani; Amelia Savira (Jurnal Al-Hikmah, 2020)
Bone-Bone Village was known as a non-smoking village in Indonesia. Bone-Bone becomes a tourist area through the district government policy. But it has limitations so that tourism potential was not developed. This study used a descriptive method with a qualitative approach. Methods of analysis used SWOT analysis. The SO strategy described that the community needs to build a road map and a masterplan for the Bone-Bone tourism area. ST’s strategy described the need for strategic cooperation between tourist areas in South Sulawesi Province. WO's strategy described the need to educate local communities about recognizing and managing the tourism potential of Bone-Bone. And the strategy of WT saw the need for strategic cooperation with private parties and investors for the development of Bone-Bone tourism area. To implement this strategy required synergies between local communities, governments, and private parties. Therefore, policy recommendations need to pay attention to human resources competence, social and cultural characteristics, and market characteristics for the advancement of tourism villages.